Impact of Climate Change on Soybean Crop Failure on the Local Economy: A Case Study in Pidie District, Indonesia - Julia Julia; Sri Handayani (Budapest International Research and Critics University, 2022)
The impact of extreme climate change significantly affects the production of various world crops. It has even caused crop failures, indirectly affecting farmers' income, thereby disrupting the realization of sustainable agriculture, which will lead to difficulties in achieving the Sustainable Development Goals. This study aimed to determine the characteristics of climate change in the area of the failed soybean crop in Pidie Regency, Indonesia. The research was carried out using a quantitative descriptive method by analyzing the data on rainfall, temperature, and humidity at the research location. The results of this study indicated that there had been a change in the type of climate in Pidie Regency from type C to type B. The average rainfall for the first period was1511.1 mm/year period had increased to 2340.2 mm/year in the second period. Characteristics of climate change affect the area of crop failure with a determinant coefficient (R2) of 0.591, meaning 59.1 % of the area of crop failure was influenced by climate characteristics. The remaining 40.9% was influenced by other factors such as selecting superior seeds, good soil management, proper fertilization, and pest control.